A Multi-Modal Discourse Analysis of #NoToJeepneyPhaseout Posts: Framing and Social Dynamics - Nikko Visperas (Asian Journal for Public Opinion Research)
In recent years, the Philippines has faced a crisis in its transportation system. It also started implementing its Public Utility Vehicle (PUV) Modernization Program to address environmental and economic concerns. Part of this is jeepney modernization, replacing the colorful, old jeeps used for public transportation with more eco-friendly vehicles; however, transport and civil groups, citizens, and the Jeepney drivers and operators oppose this implementation as this poses an anti-poor strategy that directly affects the families and livelihood of the jeepney drivers. With this, these groups and individuals support the campaign to save the jeepneys which is the focus of this study. This research employed a qualitative research design: a multi-modal discourse analysis of selected posts with the text #NoToJeepneyPhaseout and digital posters. The study unveiled frames indicating exclusion and oppression and showing unification, compassion, heroization, and cultural retention, which are manifestations of social dynamics. Given these, the utilization of critical discourse analysis and determination of social dynamics are critical for theorizing phenomena that concern social issues and the lives of groups or individuals.